2012
DOI: 10.1016/j.talanta.2011.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in explosive detection techniques

Abstract: The detection of explosives and explosive-related compounds has become a heightened priority in recent years for homeland security and counter-terrorism applications. There has been a huge increase in research within this area-through both the development of new, innovative detection approaches and the improvement of existing techniques. Developments for miniaturisation, portability, field-ruggedisation and improvements in stand-off distances, selectivity and sensitivity have been necessary to develop and impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
271
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 441 publications
(276 citation statements)
references
References 139 publications
(110 reference statements)
1
271
0
4
Order By: Relevance
“…Furthermore, recent developments in THz technologies [6,7] showed that THz waves could be a strong candidate for overcoming the obstacles associated with conventional explosives detection technologies, leading to extensive applications in security and military-related fields [7][8][9][10]. It should be noted that THz time-domain spectroscopy (THz-TDS) has been heavily utilized as the workhorse of the investigation of these capabilities of the THz regime, including the works on the detection and identification of both exposed and covered explosives through diffuse reflectance [11], investigation of the absorption spectra of numerous explosives and related compounds [12], and establishment of new spectral features within the frequency region of 3-6 THz [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent developments in THz technologies [6,7] showed that THz waves could be a strong candidate for overcoming the obstacles associated with conventional explosives detection technologies, leading to extensive applications in security and military-related fields [7][8][9][10]. It should be noted that THz time-domain spectroscopy (THz-TDS) has been heavily utilized as the workhorse of the investigation of these capabilities of the THz regime, including the works on the detection and identification of both exposed and covered explosives through diffuse reflectance [11], investigation of the absorption spectra of numerous explosives and related compounds [12], and establishment of new spectral features within the frequency region of 3-6 THz [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Trace detection utilizes either emitted vapors from the explosive or explosive particles deposited on surfaces. Some of the techniques used for bulk explosives include X-ray systems such as computed tomography (CT) that allows the characterization of materials by density, atomic number, and texture; and can be applied to personnel, luggage, large and small cargo, and vehicles [6,9,10]. X-ray diffraction (XRD) provides high specificity and very good spatial resolution for screening objects such as boxes and larger luggage.…”
Section: Detection Of Explosivesmentioning
confidence: 99%
“…The recent development of a new IMS inlet in which solid phase microextraction (SPME) can be used for the analysis of volatile compounds present in headspace systems has been used for identification of different explosive odor signatures [11]. Actually, miniaturizations of IMS devices have been widely used to detect explosives when checks are performed on passengers, baggage, vehicles, and containers [9,10 ].…”
Section: Detection Of Explosivesmentioning
confidence: 99%
See 1 more Smart Citation
“…A detecção de explosivos é importante nas investigações forenses e criminais, além do ponto de vista da saúde ambiental e da segurança [136]. Dada à importância do monitoramento dessas espécies visando à melhora da segurança militar e das análises forenses, é interessante o desenvolvimento de um método de análise simples, rápido e barato para a sua detecção e quantificação [137]. Assim, em colaboração com o aluno de iniciação cientifica João Junqueira, desenvolveu um método eletroanalítico acoplado com análise por injeção em fluxo para quantificação desse composto.…”
Section: Preâmbulounclassified